OBOWIĄZEK UDZIELENIA POMOCY W PRZYPADKU SPRZECIWU OSOBY ZAGROŻONEJ W ŚWIETLE ART. 162 KODEKSU KARNEGO - Kosonoga-Zygmunt, Julia (Zeszyty Prawnicze, 2016)
The Duty of Medical Personnel to Provide Medical Assistance to a Person In Grave Danger in the Event of His/Her Refusal to Accept Help, in the Light of Art. 162 of the Polish Criminal Code Summary The subject of this article is the refusal to accept medical assistance by a person in a condition involving a threat to his/her life or a serious health risk, and the ensuing effect this may have on the potential criminal liability of the medical and/or rescue personnel in the event of their withdrawal of assistance. The main problem is whether on the grounds of Art. 162 of the Polish Criminal Code (kodeks karny, k.k.) a patient’s refusal to accept medical assistance is relevant in criminal law, and if so, what criteria have to be met for its admission. Art. 162 of the Polish Criminal Code does not specify a general requirement of the endangered person’s consent to the administration of medical rescue services. The exceptions are those medical services for which separate provisions have been laid down requiring the patient’s consent. In the remaining scope the duty of medical and/or rescue staff to administer the assistance defined in Art. 162 § 1 is not subject to the consent of the person whose legal interest is being secured. However, this general observation does not rule out the relevance of the endangered person’s refusal to accept medical assistance and/or rescue. In particular, difficulties may arise in the assessment in the light of criminal law of the withdrawal of assistance to a suicide who refuses to have rescue services administered, although the scope of the problem is certainly much wider.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />